The Role of Da'i and Influencers in Presenting Islamic Preaching Content on Social Media Case Study: The Success of Islamic Preaching in the Younger Generation - Ilham, Ilham; Sitompul, Nurul Adha; Hasibuan, Putri; Septia, Dini; Salim, Rizky Agus (LPPPIPublishing, 2025)
This study analyzes the role of preachers and influencers in presenting da'wah content on social media and its impact on the success of da'wah among the younger generation. Using a qualitative case study approach on several popular accounts, this study found that collaboration between preachers and influencers, creative content strategies, and the use of interactive social media features contributed significantly to increasing the understanding and involvement of the younger generation in religious activities. The results also show that personal branding, theme relevance, and communication style that is close to everyday life are the keys to the success of digital da'wah.